Association of blood group with severity of dengue in a tertiary care hospital - P., Chandrakala; G. S., Krithika; S., Bhavya (International Journal of Contemporary Pediatrics, 2021)
Background: The dengue viruses belong to the family of Flaviviridae family and are arboviruses. One of the genetic factors influencing the severity is HLA antigen and ABO blood group. Methods: This was a prospective study conducted during July 2018 to May 2019 in the department of pediatrics of KIMS hospital, Bengaluru. Children between 0-18 years of age were included. The dengue serology, hemogram and blood group of these patients was investigated and compared with the severity of illness. Results: It was found that the distribution of blood groups among cases and controls were similar. However blood group O was slightly more susceptible to dengue infection (54%) than its distribution in general population (41%). In patients with primary infection, blood group O presented with milder forms of dengue (52.43%) as compared to distribution in general population (41.46%). A higher percentage of AB blood group presented as severe forms of dengue (11.63%) as compared with general population (7.32%). In patients with secondary infection, similar findings were observed. Interestingly, no cases of AB blood group presenting with secondary dengue had only mild symptoms and always presented with warning signs (0% incidence) or severe dengue. Conclusions: Dengue infection is prevalent in most parts of India with severe forms having high mortality. This study concludes that although the incidence of dengue fever is higher in children with blood group O, AB blood group is associated with severe forms of dengue, especially in secondary infections.